Screening of alcohol de-addiction potential of zinc: a study on albino rats - Gandigawad, Priya; Hiremath, Sharanabasayyaswamy B. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: With regard to tobacco and alcohol addiction, involvement of NMDA receptors and glutamate as neurotransmitter has been highlighted. Few indirect evidences support possible de-addiction potential of zinc being mediated through their interaction with nicotinic and NMDA receptors. The objectives of the present study were planned to analyze the alcohol de-addiction potential of oral zinc sulfate as a monotherapy and as a supplement to topiramate, in male wistar albino rats. Methods: Male wistar albino rats were exposed to ‘two-bottle free choice’ model of voluntary ethanol consumption, wherein each animal had access to water and 10% v/v ethyl alcohol in two separate bottles. Thirty male rats divided into five groups, each containing six rats were treated as control group, receiving 1ml/kg/d distilled water orally; zinc sulfate group receiving 18mg/kg/d of elemental zinc orally; topiramate group receiving topiramate 5mg/kg/d, orally and Topiaramate plus Zinc sulfate group receiving both zinc sulfate (18mg/kg/d) and topiramate (5mg/kg/d) orally for two weeks. Results: There were no significant differences with regard to all the three parameters in two-way ANOVA. However, there were significant differences with regard to amount of alcohol and water consumed but not API, in all the treatment groups in post-hoc test. Conclusions: It is unclear on to the alcohol de-addiction potential of zinc as monotherapy and combination therapy with topiramate.